Bioelectrical phase angle at diagnosis as a prognostic factor for survival in advanced head and neck cancer - Axelsson, Lars (Eur Arch Otorhinolaryngol, 2018)
OBJECTIVE: Bioelectrical impedance analysis (BIA) is used to measure the patient’s body composition, fat-free mass, phase angle (PA), and standardized phase angle (SPA), which are affected by malnutrition. Low values of PA and SPA have been found to be negative prognostic factors for survival in different types of cancer and other severe diseases. The aim of the current study was to investigate whether PA and SPA can be used to predict survival in head and neck (HN) cancer. METHODS: One hundred twenty-eight patients with advanced HN cancer treated in Western Sweden 2002–2006 were examined with BIA at diagnosis, and PA and SPA were calculated. Patients’ age, gender, tumor site, TNM stage, and performance status were obtained, and weight, height, and BIA were measured. Survival up to 12 years was ascertained. RESULTS: The mean PA was 5.85° and the median was 5.91°. Lower PA and SPA values were significantly associated with shorter overall survival in univariate analyses, together with higher age, oral cancer, higher T class, worse performance status, more weight loss before diagnosis, lower: weight, height, BMI, and reactance. Age, performance status, T class, and PA were significant factors for the overall survival in the multivariable analysis. A PA cutoff value at 5.95° provided the best prediction of 5-year survival. CONCLUSIONS: PA and SPA at diagnosis are significant factors for survival in patients with advanced HN cancer. They are promising prognostic tools to use in treatment planning; further studies are needed.